PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA - Anggita Mutiara Dianna Putri; Advendi Kristiyandaru; Nanik Indahwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effect of the Group Investigation (GI) cooperative learning model on learning motivation, cognitive learning outcomes, and psychomotor learning outcomes among Grade XI students in basketball material at SMAN 1 Pulung. A quantitative approach was employed using a true experimental design with a Randomized Pretest–Posttest Control Group Design. A total of 65 students were assigned through cluster random sampling into an experimental group (n=32, receiving GI instruction) and a control group (n=33, receiving conventional Direct Instruction). Data were collected using a Likert-scale learning motivation questionnaire, an essay-based cognitive test grounded in the revised Bloom's Taxonomy, and a rubric-based psychomotor skills assessment. Hypothesis testing was conducted using the Mann-Whitney U Test and Wilcoxon Signed-Rank Test at a significance level of α=0.05. The results indicated that the GI model did not produce a statistically significant effect on learning motivation (U=439.000; p=0.244; Cohen’s d=0.208), likely attributable to a ceiling effect resulting from the high baseline motivation scores in both groups. In contrast, the GI model exerted a significant and practically meaningful effect on cognitive learning outcomes (U=118.500; p<0.001; Cohen’s d=1.660, large effect) and psychomotor learning outcomes (U=318.500; p=0.005; Cohen’s d=0.776, medium effect). These findings suggest that the GI model is effective in enhancing conceptual understanding and technical skill development in Physical Education, yet requires longer intervention periods and more contextually sensitive instruments to detect meaningful motivational changes.